2022
DOI: 10.3390/polym14245432
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Biomedical Application of Polysaccharide-Based Hydrogels with a Focus on Drug Delivery Systems

Abstract: Over the last years of research on drug delivery systems (DDSs), natural polymer-based hydrogels have shown many scientific advances due to their intrinsic properties and a wide variety of potential applications. While drug efficacy and cytotoxicity play a key role, adopting a proper DDS is crucial to preserve the drug along the route of administration and possess desired therapeutic effect at the targeted site. Thus, drug delivery technology can be used to overcome the difficulties of maintaining drugs at a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 113 publications
0
20
0
1
Order By: Relevance
“…Surface modifications or functionalization of the NPs can facilitate targeted delivery to specific microbial pathogens, enhancing their antimicrobial efficacy and minimizing off-target effects. 35 In a study by Mosleh and Mahinpour, 102 CeVO 4 nanoparticles were synthesized using a sonochemical route, and their photocatalytic properties were evaluated using the degradation of methyl orange (MO) under ultraviolet light irradiation. The results showed that the as-prepared CeVO 4 nanoparticles exhibited excellent photocatalytic activity.…”
Section: Advantages Of Cevo 4 Nps Over Conventional Antibiotics or An...mentioning
confidence: 99%
“…Surface modifications or functionalization of the NPs can facilitate targeted delivery to specific microbial pathogens, enhancing their antimicrobial efficacy and minimizing off-target effects. 35 In a study by Mosleh and Mahinpour, 102 CeVO 4 nanoparticles were synthesized using a sonochemical route, and their photocatalytic properties were evaluated using the degradation of methyl orange (MO) under ultraviolet light irradiation. The results showed that the as-prepared CeVO 4 nanoparticles exhibited excellent photocatalytic activity.…”
Section: Advantages Of Cevo 4 Nps Over Conventional Antibiotics or An...mentioning
confidence: 99%
“…Hydrogels have gained the most attention of any biomaterials discovered in recent decades on the basis of their superior biodegradability, biocompatibility, and responsiveness 19 . A hydrogel is a three-dimensional molecule made up of soft, crosslinked components which are non-water soluble.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides, which are the most abundant biopolymers found in nature, have attracted considerable attention as promising candidates for the development of next-generation “smart” biomaterials for application in various fields including drug delivery and wound dressings technology [ 9 ]. The unique properties of these sugar-based biopolymers include their high biocompatibility, biodegradability, absorption capacity, as well as the presentation of multiple functional sites of high chemical reactivity, which allow their facile derivatization and functionalization [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%